Methanol intoxication with putaminal and white matter necrosis: MR and CT findings. - Rubinstein, D; Escott, E; Kelly, J P (American Journal of Neuroradiology, 1995)
We report a case of methanol intoxication in which the initial CT scans appeared normal. MR at 4 days showed the typical putaminal lesions of methanol intoxication and, in addition, peripheral white matter lesions that spared a thin rim of subcortical white matter. A CT scan at 17 days showed the putaminal and white matter lesions. The white matter lesions correspond well to lesions previously described in pathologic specimens.